Inhibitors to EFL teachers' reflective teaching and EFL learners' reflective thinking and the role of teaching experience and academic degree in reflection perception. Issue 1 (2nd January 2018) - Soodmand Afshar, Hassan; Farahani, Mojtaba
Abstract: The present study investigated Iranian English as a Foreign Language (EFL) teachers' perception of their own reflective teaching, of inhibitors to their reflective teaching, of inhibitors to their students' reflective thinking, and the impact of teaching experience and academic degree on their perception of reflective teaching. To this end, 304 private-language-institute English as a Foreign Language Teachers teachers participated in the study by completing English Language Teaching Reflection Inventory developed by Akbari, Behzadpoor, and Dadvand, Inhibitors to EFL Teachers' Reflective Teaching Questionnaire and Inhibitors to EFL Learners' Reflective Thinking Questionnaire, with the last two instruments being developed and validated by the researchers. The results indicated that (1) Iranian EFL teachers perceived their reflective teaching to lie at a medium level, (2) three types of inhibitors to EFL teachers' reflective teaching included 'lack of knowledge', 'affective-emotional' and 'teaching situation' inhibitors, and (3) three types of inhibitors to EFL learners' reflective thinking also comprised 'affective-emotional', 'cognitive' and 'learning situation' inhibitors. The results of two-way ANOVA indicated both academic degree and teaching experience significantly differentiated Iranian EFL teachers with respect to their reflective teaching perception, but the interaction effect of them did not do so. The results are discussed in detail in the article.